Analisis Hukum Keluarga Islam Terhadap Pasal 4 Ayat (2) Peraturan Pemerintah Nomor 45 Tahun 1990 tentang Izin Perkawinan dan Perceraian Bagi Pegawai Negeri Sipil - Rofi'i, Hilmi Yusron; Zaki, H. Muhammad; Faizal, Liky; Qohar, Abd. (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The purpose of this study was to analyze the reasons why female civil servants were prohibited from becoming second, third and fourth wives based on Government Regulation Number 45 of 1990; and to analyze based on Islamic family law against the prohibition of female civil servants to become second, third and fourth wives based on Government Regulation Number 45 of 1990. The results of this study are the Prohibition of Women Civil Servants from becoming the third and fourth second wife is a preventive measure to prevent women who are civil servants from disputes in the family, prevent women from psychological pressure caused by polygamy has an impact on changing attitudes so that can interfere with their performance as a civil servant, to prevent children from psychological pressure that results in children's future growth, and protect the rights of wives and children regarding civilization in the event of a divorce in a polygamous marriage which can harm a woman with a civil servant status and result in imperfect rights support the child. The prohibition of women who are civil servants from becoming the second third and fourth wives in Government Regulation Number 45 of 1990 is in accordance with the maqashid sharia, namely to protect the soul (hifdz nafas) and protect the offspring (hifdz nasl), namely to protect children from the consequences If a civil servant woman becomes a polygamous wife